Media Pembelajaran Tata Busana Di SMK PGRI Batang - Aya Sophia (CV. ITTC INDONESIA, 2024)
SMK PGRI Batang in the Fashion Design vocational in learning pattern making is known to have no learning media in the form of multimedia that can facilitate teachers and students in learning pattern making. Pattern making learning activities with a predetermined duration are often insufficient learning time, so they cannot accommodate all student desires which can cause pattern making learning not to run according to learning targets. So that learning aids are needed that can be used anytime and anywhere. This learning media is designed using Construct 2. The system development method used is the multimedia system development method version of Sutopo which consists of 6 stages, namely concept, design, material collection, manufacture, testing, and distribution. Testing uses the graphical user interface (GUI) method, and user acceptance test (UAT). The results of this learning media can help users as a tool in learning basic patterns, including in making patterns for skirts, jackets, tunics, pants, and children's clothing. This application can be used anywhere and anytime because the application is offline-based, in the application there are examples of pattern images that can be downloaded by watching the existing pattern making tutorial.